2015
DOI: 10.1007/s00702-015-1411-7
|View full text |Cite
|
Sign up to set email alerts
|

Early processing of emotional faces in a Go/NoGo task: lack of N170 right-hemispheric specialisation in children with major depression

Abstract: Emotionally biased information processing towards sad and away from happy information characterises individuals with major depression. To learn more about the nature of these dysfunctional modulations, developmental and neural aspects of emotional face processing have to be considered. By combining measures of performance (attention control, inhibition) in an emotional Go/NoGo task with an event-related potential (ERP) of early face processing (N170), we obtained a multifaceted picture of emotional face proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…To fully capture the treatment-related changes in behavior, composites previously associated with this type of task were utilized (Casey, 2007; Schulz et al, 2007; Tottenham et al., 2010; Tottenham et al, 2011). The emotional go/no-go task has been validated for use with adults (Hare et al, 2008), as well as community and clinical samples of children and adolescents (Grunewald et al, 2015; Hare et al, 2008; Ladouceur et al, 2006; Tottenham et al, 2010; Tottenham et al, 2011). It has not been previously used in a forensic population.…”
Section: Methodsmentioning
confidence: 99%
“…To fully capture the treatment-related changes in behavior, composites previously associated with this type of task were utilized (Casey, 2007; Schulz et al, 2007; Tottenham et al., 2010; Tottenham et al, 2011). The emotional go/no-go task has been validated for use with adults (Hare et al, 2008), as well as community and clinical samples of children and adolescents (Grunewald et al, 2015; Hare et al, 2008; Ladouceur et al, 2006; Tottenham et al, 2010; Tottenham et al, 2011). It has not been previously used in a forensic population.…”
Section: Methodsmentioning
confidence: 99%
“…Depression is defined by American Psychiatric Association (APA) as a disorder which influences the function and daily life of and individual and which becomes prominent with loss of attention, sleep disorder, change of appetite-weight, exhaustion, psychomotor retardation, insignificance, guilt, attention problems and thought of death (Köroğlu, 2013;Sadock & Sadock, 2009;Türkçapar, 2013). As it is thought to be a disorder generally occurring after twenties, recent studies show that the roots of depression goes back to childhood and it is the most important and common problem encountered particularly in puberty (Cimino et al, 2015;Costello, Erkanli & Angold, 2006;Grunewald et al, 2015;Hamrin & Pachler, 2005;Lewinson et al, 2000;James, Wotton, Duffy, Hoang, & Goldacre, 2015;Şimşek, 2015). That is to say, studies dealing with depression in children and adolescents show that it is common among the children and adolescents between the rates of % 1-6 and % 20 (Bilal, 2005;Eskin, 2000;Grunewald et al, 2015;Gröholt et al, 2000;James et al, 2015;Lewinson et al, 2000;Sadock & Sadock, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As it is thought to be a disorder generally occurring after twenties, recent studies show that the roots of depression goes back to childhood and it is the most important and common problem encountered particularly in puberty (Cimino et al, 2015;Costello, Erkanli & Angold, 2006;Grunewald et al, 2015;Hamrin & Pachler, 2005;Lewinson et al, 2000;James, Wotton, Duffy, Hoang, & Goldacre, 2015;Şimşek, 2015). That is to say, studies dealing with depression in children and adolescents show that it is common among the children and adolescents between the rates of % 1-6 and % 20 (Bilal, 2005;Eskin, 2000;Grunewald et al, 2015;Gröholt et al, 2000;James et al, 2015;Lewinson et al, 2000;Sadock & Sadock, 2009). Starting from this evidence, it can be said that childhood depression is an important and serious psychological disorder for children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…However, much research has also found no difference in the error rates of No-Go responses between patients with MDD and healthy individuals. For example, Grunewald et al (2015) found both MDD patients and healthy controls showed lower error rates in happy rather than sad or neutral No-Go trials. Colich et al (2015) found no group difference in the error rate for emotional No-Go trials behaviorally but revealed that only depressed adolescents showed less activation in the dorsolateral prefrontal cortex for inhibiting No-Go targets that followed a sad rather than happy face.…”
Section: Introductionmentioning
confidence: 99%